Diritti, Europa, Federalismo Bruno Trentin in prospettiva transnazionale (1988-2007) - Cruciani, Sante; Del Rossi, Maria Paola (Studi e saggi, 2023)
Based on a research project of the University of Tuscia and of the Alta Scuola SPI-CGIL, the volume delves into Bruno Trentin's intellectual and political thought, from the CGIL General Secretary to his role in the European Parliament. A network of transnational relationships emerges, stretching from the USA to Europe, from Latin America to South Africa, from the Mediterranean to the Middle East. The 'Sindacato dei Diritti' and the European project of the CGIL are thus transferred into the socialist family, in line with Delors' proposal of a Federation of Nation States, and into the battle of the 'Spinelli Group' in favour of the coordination of economic and social policies, of the European Constitution, and of a united Europe in foreign policy and defence. The volume is enriched by unpublished documents in Italian, French, English and Spanish.